Search for type-III Seesaw heavy leptons in pp collisions at s√=8 TeV with the ATLAS Detector - Aad, G. (2015)
A search for the pair-production of heavy leptons (N0 , L±) predicted by the type-III seesaw theory formulated to explain the origin of small neutrino masses is presented. The decay channels N0 → W±l ∓ (` = e, µ, τ ) and L ± → W±ν (ν = νe, νµ, ντ ) are considered. The analysis is performed using the final state that contains two leptons (electrons or muons), two jets from a hadronically decaying W boson, and large missing transverse momentum. The data used in the measurement correspond to an integrated luminosity of 20.3 fb−1 of pp collisions at √ s = 8 TeV collected by the ATLAS detector at the LHC. No evidence of heavy lepton pair-production is observed. Heavy leptons with masses below 325–540 GeV are excluded at the 95% confidence level, depending on the theoretical scenario considered